A versatile integrated tube for rapid and visual SARS-CoV-2 detection - Xu, Jingsong; Wang, Xi; Yang, Shuang; He, Lei; Wang, Yuting; Li, Jiajun; Liu, Qian; Li, Min; Wang, Hua (Frontiers in Microbiology, 2023)
The coronavirus disease 2019 (COVID-19) caused by novel severe acute respiratory coronavirus 2 (SARS-CoV-2) has been rapidly spreading worldwide. Rapid and widespread testing is essential to promote early intervention and curb the ongoing COVID-19 pandemic. Current gold standard reverse transcription-polymerase chain reaction (RT-PCR) for detecting SARS-CoV-2 is restricted to professional laboratories and well-trained personnel, thus, limiting its widespread use in resource-limited conditions. To overcome these challenges, we developed a rapid and convenient assay using a versatile integrated tube for the rapid and visual detection of SARS-CoV-2. The reaction conditions of the method were optimized using SARS-CoV-2 RNA standards and the sensitivity and specificity were further determined. Finally, it was verified on clinical specimens. The assay was completed within 40 min, and the result was visible by the naked eye. The limits of detection (LODs) for the target ORF1ab and N genes were 50 copies/µL. No cross-reactivity was observed with the RNA standard samples of four respiratory viruses or clinical samples of common respiratory viral infections. Ninety SARS-CoV-2 positive and 30 SARS-CoV-2 negative patient specimens were analyzed. We compared these results to both prior and concurrent RT-PCR evaluations. As a result, the overall sensitivity and specificity for detection SARS-CoV-2 were 94.5% and 100.0%, respectively. Conclusions: The integrated tube assay has the potential to provide a simple, specific, sensitive, one-pot, and single-step assay for SARS-CoV-2.